(untitled) (Stato, Chiese e pluralismo confessionale, 2023)
The Tragic Choices during the Covid Health Emergency: When the Resources are Limited, Who Should be Cured First among Several Patients? A Comparative Law Analysis SOMMARIO: 1. Introduzione - 2. L’approccio italiano: le raccomandazioni di etica clinica della SIAARTI e le linee guida SIAARTI-SIMLA - 3. La gestione della scarsità di risorse sanitarie a livello comparato - 4. Considerazioni (finali) comparatistiche - 5. Uno sguardo verso il futuro. ABSTRACT: During the Covid-19 health emergency, a situation of scarcity of resources of different nature, albeit all somehow connected with the “medical world” (e.g. nurses and doctors), dramatically unfolded. This organisational “catch-22” induced the SIAARTI (the Italian Medical Society) to issue some recommendations of clinical ethics. The last ones turn out to be the subject matter of multiple criticisms: given the potential criteria of allocation of resources, one of those adopted the chronological one. Starting from this reflection, the paper discusses and analyses, from a comparative perspective, the approach taken by further countries: in this respect the demarcation lines existing between the Italian responses to the pandemic and those coming from other European - but not EU, namely Switzerland and the United Kingdom - countries will be highlighted.